Promotion, Innovation, and Product Quality towards Purchase Decisions of Sukoharjo Batik Cloth during Covid-19 Pandemic - Veronica Vivi Novianti Kusuma Putri; Yusepaldo Pasharibu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Covid-19 pandemic has an impact on all sectors, one of which is the economy, which affects MSMEs in Indonesia, especially batik cloth craftsmen in Sukoharjo. Several strategies to make purchasing decisions for business continuity carried out by these entrepreneurs include promotion, innovation, and creating quality products.This study aims to analyze and determine the effect of promotion, innovation and product quality on purchasing decisions on Sukoharjo batik cloth. The sample of this study was as many as 200 respondents obtained by purposive sampling technique using a questionnaire. The criteria for respondents are those who have bought Sukoharjo batik cloth. Hypothesis testing using multiple linear regression technique. The results showed that promotion and product quality proved to have an effect on purchasing decisions, but innovation had no effect on purchasing decisions.